Організація бастіонних укріплень території середмістя та передмість Львова у XVII ст. - Оконченко, О. М.; Оконченко, І. В. (Видавництво Львівської політехніки, 2013)
Окреслено умови і причини виникнення бастіонних укріплень у Львові у XVII ст. Проаналізовано історичні плани і карти Львова стосовно інформації про рівень реалізації, авторство та стильову приналежність проектованих укріплень XVII ст. Висвітлено маловідому схему бастіонних укріплень Львова. З'ясовано, що до нашого часу збереглися залишки реалізованих укріплень у староголландській школі бастіонної архітектури. Conditions and reasons for emergence of bastion fortifications in Lviv of the 17th c. are outlined in the article. Historical schemes and maps of Lviv concerning the information about the level of realization authorship and stylistic reference of 17th c. fortification projects have been analized. Less known scheme of Lviv bastion fortifications is highlighted. It has been ascertained that remnants of the realized fo rtifications of Old Dutch school of bastion architecture have been preserved up to the present.
Keywords: Львів; оборонна архітектура; історичні плани; система фортифікацій; бастіони; Lviv; military architecture; historical schemes; fortifications; system of fortifications; bastions